SYSTEMATIC LITERATURE REVIEW: THE IMPLEMENTATION OF THE CREATIVE PROBLEM SOLVING LEARNING MODEL IN RELATION TO STUDENTS' CREATIVE THINKING ABILITY - Soraya, Selfina; Hartono, Hartono; Fajriah, Noor; Sidi, Noraidah binti (Jurnal Pendidikan Matematika dan IPA, 2025)
It is important to develop student"™s mathematical creative thinking skill. Increasing students' mathematical creative thinking skills can occur in learning, one of which is learning with the Creative Problem Solving (CPS) model. This study aims to find out he application of the CPS learning model to improving students' mathematical creative thinking skills. The method used is a literature review, with 15 articles reviewed. The result are: 1) the CPS learning model is proven to be able to improve creative thinking skills, problem solving, and adaptive reasoning; 2) the CPS learning model uses four stages, namely: problem classification, expressing opinions, evaluation and selection, and implementation. During the learning process with the CPS model, it is necessary to create a conducive environment. CPS learning model is effective in enhancing students' creative thinking skills, particularly in mathematics education. Most studies implement four main stages: problem clarification, idea generation, evaluation, and implementation. The application of CPS demonstrates flexibility, with the number of steps ranging from three to eight depending on context and teacher innovation. Successful implementation is influenced by student motivation, time management, and a conducive learning environment. Findings consistently indicate that CPS fosters higher creativity compared to conventional learning models.